2017
DOI: 10.1038/nrneph.2016.186
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming and tolerance during sepsis-induced AKI

Abstract: The host defence against infection is an adaptive response in which several mechanisms are deployed to decrease the pathogen load, limit tissue injury and restore homeostasis. In the past few years new evidence has suggested that the ability of the immune system to limit the microbial burden — termed resistance — might not be the only defence mechanism. In fact, the capacity of the host to decrease its own susceptibility to inflammation- induced tissue damage — termed tolerance — might be as important as resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(121 citation statements)
references
References 81 publications
2
115
0
4
Order By: Relevance
“…Once activated, these SIRTs play the dominant role in the development of a hypo-inflammatory state and an environment of metabolic downregulation and reductions in glycolysis and TCA-induced oxidative phosphorylation characterised by mitochondrial ATP production via fatty acid oxidation (Gómez et al 2017; Vachharajani et al 2016). This adaptive low-energy state is often described as cellular ‘hibernation’ (Levy et al 2005; Liu et al 2011a; Singer 2008) (reviewed (Singer 2017)) and it is important to stress that this phenomenon is not limited to macrophages and monocytes but also takes place in hepatocytes and striated muscle cells (Carré and Singer 2008; McCall et al 2011; Singer 2007, 2008).…”
Section: Consequences Of Chronic Systemic Iandonsmentioning
confidence: 99%
“…Once activated, these SIRTs play the dominant role in the development of a hypo-inflammatory state and an environment of metabolic downregulation and reductions in glycolysis and TCA-induced oxidative phosphorylation characterised by mitochondrial ATP production via fatty acid oxidation (Gómez et al 2017; Vachharajani et al 2016). This adaptive low-energy state is often described as cellular ‘hibernation’ (Levy et al 2005; Liu et al 2011a; Singer 2008) (reviewed (Singer 2017)) and it is important to stress that this phenomenon is not limited to macrophages and monocytes but also takes place in hepatocytes and striated muscle cells (Carré and Singer 2008; McCall et al 2011; Singer 2007, 2008).…”
Section: Consequences Of Chronic Systemic Iandonsmentioning
confidence: 99%
“…The function of Muc1/MUC1 in kidney has been more difficult to address as direct infection by bacteria and virus is much less common. While sepsis does stress the kidney primarily by indirect means, the most well characterized model of acute kidney injury is produced by clamping both the renal artery and vein, or the artery alone, to produce ischemia, and studying recovery of kidney function and morphology after return of blood flow for hours to days [28-30]. Using this approach, we found that Muc1 is protective in the kidney in a mouse model of ischemia-reperfusion injury by transactivation of the HIF-1 and β-catenin protective pathways [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…This has been considered a result of metabolic adaptation [37]. Metabolic adaptation is like a protective response to inflammation.…”
Section: The Role Of Crrt In Inflammation and Metabolic Adaptation Inmentioning
confidence: 99%
“…Metabolic adaptation is like a protective response to inflammation. It increases the circulating levels of glucose by stimulating glycogenolysis and gluconeogenesis [38] and switches metabolism from regulatory energy pathways toward aerobic glycolysis, similar to the Warburg effect in cancer cells [37]. The elevated glucose enables the elevation of aerobic glycolysis in immune cells, which provide metabolic intermediates necessary for the expansion of biomass in immune cells and promotion of tissue repair [39].…”
Section: The Role Of Crrt In Inflammation and Metabolic Adaptation Inmentioning
confidence: 99%